Improved blockchain-based ECDSA batch verification scheme - Wu, Guangfu; Zhou, Jiandong; Fu, Xiaoyan (Frontiers in Blockchain, 2025)
IntroductionBlockchain technology has attracted much attention due to its decentralization, transparency and security. Initially applied in the financial field, it has now expanded to various fields such as Internet of Things (IoT), electronic cash and healthcare. However, the open nature of blockchain has raised potential security concerns about sensitive transaction data, and the increasing number of transactions requires low-latency solutions. Most blockchain applications still rely on the lightweight Elliptic Curve Digital Signature Algorithm (ECDSA). Due to complex operations such as vectorized multiplication and modular inversion, this may introduce significant additional overhead.MethodsTo address these issues, a new scheme named KTP-ECDSA is proposed. This scheme is based on the improved two-parameter Elliptic Curve Digital Signature Algorithm (TP-ECDSA) and the KGLP algorithm. In both the signing and verification processes, this scheme eliminates modular inverse operations and reduces scalar multiplications during the verification stage by using batch verification.ResultThe experimental results show that, compared with the traditional ECDSA, KTP-ECDSA has achieved a speed increase of over 50% in both independent verification and batch verification, significantly improving the efficiency of signature verification.DiscussionBy adopting the KTP-ECDSA algorithm and using the digital signature batch verification method, multiple signatures can be verified simultaneously, thus reducing the computational burden of the traditional single-verification method. This greatly increases the overall transaction throughput and improves resource utilization efficiency.